Strategic Partnership to Promote Climate-Smart Agriculture in Kenya: Consultative Workshop on Annual Work Plan Development - Osumba, Joab J.L.; Recha, John W.M.; Kawira, Tracy; Radeny, Maren A.O. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate change remains a significant factor impacting agriculture in sub-Saharan African countries, including Kenya. The concentration of greenhouse gases is the primary cause of climate change in the world and human activity is the reason for the accumulation of these gases. In its Nationally Determined Contribution (NDC), Kenya committed to implementing climate-smart agriculture (CSA) measures to address these climate change impacts and meet her obligations to the Paris Agreement in reducing emissions of greenhouse gases.